Transtracheales Monitoring des Nervus laryngeus recurrensDer Prototyp eines neuen Tubus - Lamadé, Wolfram; Meyding-Lamadé, Uta; Hund, Ernst; Senninger, Norbert; Herfarth, Christian (Der Chirurg, 1997)
A new sensing device for the continuous intraoperative monitoring of the recurrent laryngeal nerve is presented. It is based on a double ballooned endotracheal tube including stimulating and tracing electrodes. The system is characterised by three advantages: 1) it is atraumatic, 2) it is operating completely outside the operating field (extraterritorially), 3) nerve function is being monitored continuously from the time of intubation to the time of extubation. The presented system has been evaluated in piglets. First results in humans will be available shortly.